Audience Reception Analysis of Sexual Education in the Film Dua Garis Biru - Stefanus Andriano; Elvina Estelita Pasaribu (Ikatan Sarjana Komunikasi Indonesia, 2026)
The film Dua Garis Biru (2019) is an Indonesian production that addresses social issues surrounding adolescent sexuality within the teenage drama genre. The film follows a high school couple whose decision to engage in premarital sex leads to severe consequences, including unplanned pregnancy and compromised futures. This issue highlights a widespread lack of understanding regarding sex and reproductive education, which ultimately yields negative impacts. This study aims to analyze the reception of undergraduate student audiences from three Indonesian universities after watching Dua Garis Biru, as well as their comprehension of the sex education messages conveyed through narrative scenes. Utilizing Stuart Hall’s reception theory with a descriptive qualitative approach, data were gathered from five informants through in-depth interviews to determine their decoding positions, supplemented by document analysis. The findings indicate that all five informants adopted a dominant-hegemonic position, with no informants falling into the negotiated or oppositional positions. They agreed that Dua Garis Biru successfully delivers both entertainment and education, addresses youth social issues, and opens up discussions on sex education, which is still widely considered taboo. Hopefully, this film can provide inspiration and shift public perception regarding the vital importance of sex education.